(untitled) (Journal of Economic Research & Business Administration, 2016)
In the conditions of the competitive environment many firms try to ad-here to balance in desire to satisfy both requirements of the organization, and need of the consumer. Almost all enterprises enable the realization of finished goods and goods on the terms of a delay of payments for the pur-pose of an operating time of long-term communications with buyers and customers, and also for increase in commodity turnover of the enterprise. Therefore normal functioning of firm can’t be presented without formation of receivables. However uncontrolled emergence of this asset results in deficiency of money as the means received from debtors are one of the most significant articles of the income of the enterprise. In turn shortage of money and their equivalents increases need of the organization for current assets for financing of the current activity, can negatively affect a financial condition of the enterprise, worsen liquidity and solvency of the organiza-tion, to increase its financial dependence and, as a result to reduce busi-ness activity of firm.